Science, authorship and truth in statements of the movement ‘escola sem partido’: The mechanism of denouncement - Katz, Elvis Patrik; Mutz, Andresa Silva da Costa (FCL-UNESP Laboratório Editorial, 2020)
The movement Escola Sem Partido has become known in recent years, in Brazil, for launching successive attacks of power against the teaching category. For such an undertaking, it was necessary, among other actions, to create a set of knowledges which gave them certain legitimacy in the field of Education. In this paper, we analyzed from the theoretical reference from the Cultural Studies and inspired by the ideas of Michel Foucault, what we named as the denouncement mechanism, a strategy established in order to represent the movement as true and necessary to our time. The empirical material selected for this research consisted of 127 articles taken from the site escolasempartido.org. The investigation allowed us to verify the way Escola Sem Partido operates in the construction of discourse which points to a supposed hegemony of ideological indoctrination in schools, engaging in a dispute for truth in a process in which it rivaled even the academic literature itself.